Performance Evaluation of The Kacang Pedang Retention Pond as A Flood Control Effort in Pangkalpinang City - Irene Tresna Wiati; Hendi Hendra Bayu (Journal of Civil Engineering and Planning (JCEP), 2026)
Retention ponds are one of the important infrastructures in flood control in Pangkalpinang City, but the effectiveness of retention pond performance has decreased along with changes in initial conditions, hydrology, and land use. This study aims to analyze the existing retention ponds, the decline in effectiveness and sustainable mitigation of flood control in Pangkalpinang. The research methods are hydrological evaluation, spatial GIS, existing ponds and recommendations. Data analysis includes pond techniques, rainfall, watershed, land use, geometry and pond capacity. The results showed that the pond capacity decreased by 10.42% due to sedimentation, inappropriate geometric and hydrological designs and changes in land use so that the pond is not effective in controlling floods. Based on these findings, sustainable optimization and mitigation strategies include sediment management, capacity and design evaluation, increasing the integration of ponds and urban drainage, and the need for spatial-based retention pond management.